Training spatial abilities : a workbook for students of architecture - Gerber, Andri (2020)
It has been shown that spatial perception can be improved through practice. Opportunities to offer such practice are offered in this workbook, which was tested by nearly one thousand architecture students before publication, and emerged from an academic study funded by the Swiss National Science Foundation, conducted jointly by the Zurich University of Applied Sciences (ZHAW) and the ETH Zurich. The book contains 90 exercises that work with architectural elements but can be mastered without prior knowledge, plus a section with solutions and explanatory texts by experts from theory and practice by M. Berkowitz, D. Dietz, B. Emo, A. Gerber, Chr. Hölscher, P. Holgate, St. Kurath, C. Leopold, D. Schulz, Th. & N. Shipley, E. Stern, D. Uttal.
Includes bibliographical references.
Keywords: Space (Architecture) -- Problems, exercises, etc; Space perception -- Problems, exercises, etc; Space (Architecture); Space perception; Problems and exercises